Work Posture Analysis in The Chips Frying Section Using Workplace Ergonomic Risk Assessment Method - Tania, Tania Journal; Erliana, Cut Ita; Zakaria, Muhammad (International Journal of Engineering, Science and Information Technology, 2024)
U.D. Keripik Mustika is a small and medium enterprise (SME) that processes yam raw materials into special snacks in great demand for consumption and souvenirs. According to observations, the worker experienced pain complaints during frying in the shoulder area, arms, back, waist, hands, and feet. The complaint experienced by this worker was due to the worker's posture that had to stand and bend slightly with the position of the hands continuously mixing for 7 hours a day and done manually repeatedly over long periods. This is if left, then the worker will suffer musculoskeletal disorders (MSDs). The research was conducted using the WERA method (Workplace Ergonomic Risk Assessment), which explains the development of ergonomic risk assessment at the workplace to detect physical risk factors associated with musculoskeletal disorders (MSDs). The spread of the Nordic Body Map questionnaire on frying workers showed pain complaints from an unergonomic working posture. The study results were obtained from Employee 1, with a physical indicator score of 39 (Medium), and Employee 2, with a physical indicator score of 37 (Medium). Therefore, there is a need for improvement of the work facilities or the worker's posture. Based on the assessment results, the researchers suggested additional facilities for workers to design standing aids that reduce pain in the leg muscles and complaints of Musculoskeletal Disorders (MSDs).